Memory laws in vulnerable societies - Vučić, Mihajlo (Sociološki pregled, 2022)
The paper explores the connection between memory laws and the historical interpretation of conflict in certain societies. The author uses the analytical concept of vulnerable society to define the research subject. Vulnerable societies have experienced conflicts in the past, but they cannot reach a consensus on the nature, causes, and consequences of the conflict. The research is based on the analysis of memory laws in several types of vulnerable societies. The Holocaust is used as a reference point, a crime that transcends the national historical interpretations due to its universal symbolic nature. The case studies are divided into three parts: French colonial and revolutionary past, memory wars in Eastern Europe, and a comparative overview of societies that experienced civil wars. The analysis of the case studies leads to the conclusion that memory laws in vulnerable societies act as a catalyst of conflicts, instead of fulfilling their primary purpose of social stabilization.
Keywords: memory laws; conflict; civil war; crimes; history